The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1590/s0103-84782004000100026
|View full text |Cite
|
Sign up to set email alerts
|

Intoxicação de vacas leiteiras por farelo de algodão naturalmente contaminado com aflatoxinas

Abstract: Aflatoxina M1 é um dos metabólitos tóxico da aflatoxina B1, excretada pelo leite de animais que ingerem alimentos contaminados. O presente trabalho descreve o caso de uma fazenda produtora de leite na região de Itú, São Paulo, onde os animais foram alimentados com farelo de algodão naturalmente contaminado com as aflatoxinas. As aflatoxinas B1, B2, G1 e G2 foram identificadas por CCD e quantificadas por fotodensitometria nas concentrações de 43,5; 15,2; 9,1 e 8,6ng.g-1 respectivamente. O leite destes animais f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 7 publications
0
6
0
3
Order By: Relevance
“…The supplementation of SCFP (S. cerevisiae fermentation product) consisting of yeast cells has been shown to increase DMI and milk yield, as well as milk fat and protein yield, in lactating dairy cows [42,45]. However, milk yield was decreased 3.0 L/day and concentration of milk fat and protein decreased after dairy cows were fed 43.5-120.0 µg of AFB 1 /kg of BW [48]. The reduction in milk protein concentration may be a consequence of the inhibition of microbial protein synthesis by AFB 1 [28].…”
Section: Effect On Feed Intake Nutrient Digestibility and Animal Permentioning
confidence: 99%
“…The supplementation of SCFP (S. cerevisiae fermentation product) consisting of yeast cells has been shown to increase DMI and milk yield, as well as milk fat and protein yield, in lactating dairy cows [42,45]. However, milk yield was decreased 3.0 L/day and concentration of milk fat and protein decreased after dairy cows were fed 43.5-120.0 µg of AFB 1 /kg of BW [48]. The reduction in milk protein concentration may be a consequence of the inhibition of microbial protein synthesis by AFB 1 [28].…”
Section: Effect On Feed Intake Nutrient Digestibility and Animal Permentioning
confidence: 99%
“…They usually are ingredients very susceptible to contamination by mycotoxins and toxigenic fungi. Presence of mycotoxins in food for animal consumption was reported in different regions of Brazil (Sassahara et al, 2003;Gonçalez et al, 2004;Oliveira et al, 2008). A. flavus capable of producing CPA and aflatoxins were isolated from feed samples studied in this work (Silva et al, 2015).…”
Section: Resultsmentioning
confidence: 80%
“…Although most references in the literature report the presence of aflatoxin M1 in cow milk (Dorner et al, 1994;Galvano et al, 1996;Gonçalez et al, 2004;Oliveira et al, 2008), it is known that this toxin can easily occur in milk of sheep, goats, buffaloes and camels (Galvano et al, 1996;Motawee et al, 2009), but there are few reports about the presence of aflatoxin M1 in goat milk (Oliveira et al, 2007). Co-occurrence between AFM1 and CPA in bovine milk has been the subject of studies by other authors (Oliveira et al, 2008;Rosemaninho et al, 2006), however there are no reports about CPA in goat milk.…”
Section: Introductionmentioning
confidence: 99%
“…However, a few studies have reported contradictory results for the effects of AFB 1 on milk yield and composition. Gonçalez et al (2004) observed that 76.4 μg/kg of aflatoxins in the diet (43.5 μg of AFB 1 ) of dairy cows for 6 mo was sufficient to reduce the milk yield. Similar findings were reported by Queiroz et al (2012), with cows receiving 75 μg of AFB 1 /kg during a period of 12 d having lower levels of milk fat and protein.…”
Section: Introductionmentioning
confidence: 96%